Potential LBO of CTS corp: business plan, exit and returns - Castell-Rüdenhausen, Casimir Friedrich Wilhelm Graf Zu (2020)
The following paper focuses on the development of a business plan, exit strategy and calculation of returns for the potential LBO of CTS Corporation, a US-based electronic component manufacturer that serves OEMs infive differentend markets. It develops the business plan by clearly showing growth and cost drivers, presents theentry valuation and returns and defines aclear exit strategy in an effortto simulatea section of areal-life Investment Committee Paper.